The Analysis of Prepositional Phrases in Analytical Exposition Texts “Why is Social Distancing Important during Corona Pandemic?” and “The Importance of Wearing Mask during COVID-19 Pandemic Era” - Yenita Uswar; Ikhawanul Mubarrak Lubis (Universitas Potensi Utama, 2022)
Language is a communication tool to express human feelings and thoughts. Learning one of texts that is Analytical Exposition Texts in important in English Lesson. Analytical Exposition text is basically an opinion writing about a phenomenon or event. This paper is one type of Argumentation Text which explains the thoughts of the author. The researcher analysed one of parts of speech that was in the Analytical Exposition, was preposition, and the analysis of preposition is using syntactic form in where preposition had to related to other words and it called Prepositional Phrases. The researcher chosen two texts of Analytical Exposition Text “Why is Social Distancing Important during Corona Pandemic?